Analisis Implementasi Kurikulum Merdeka Pada Kegiatan Pembelajaran Intrakurikuler Dan Kokurikuler di SD N Jumeneng Kabupaten Sleman - Rosjanah, Nisa; Kiptiyah, Siti Maryatul (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Merdeka Curriculum is a new curriculum that aims to improve the 2013 curriculum. This purpose of the research is to describe the implementation of the Merdeka Curriculum in intracurricular and co-curricular learning activities in elementary school, as well as the obstacles and solutions applied by the teachers to overcome obstacles to the implementation of the Merdeka Curriculum. The research method used is descriptive qualitative. The data collection techniques used include observation, interviews, questionnaires, and documentation. The data analysis techniques used the Miles and Huberman analysis model which consists of data reduction, data display, and conclusion drawing or verification. The result showed that the implementation of the Merdeka Curriculum at Jumeneng State Elementary School was good but there were still obstacles that made the implementation not optimal. The Merdeka Curriculum’s intracurricular and co-curricular learning consists of preparation, implementation, and evaluation. Teacher constraints at the planning stage is that teachers don’t always compile teaching modules and don’t carry out diagnostic asessments. Teachers haven’t implemented differentiated instruction and project-based learning. Evaluation is conducted at the end of the chapter and the end of semester summative. School readiness in implementing P5 co-curricular is still at the initial stage. The main obstacle is teacher readiness due to the low level of teacher’s abilities, skills, and competencies in implementing Merdeka Curriculum. The solutions offered are training, socialization, technical guidence, and teachers sharing sessions.